The Promise of Catholic Schools for Educating the Future of Los Angeles - Litton, Edmundo F.; Martin, Shane P.; Higareda, Ignacio; Mendoza, Julie A. (Catholic Education: A Journal of Inquiry and Practice, 2010)
This study examined the impact of Catholic education on elementary and secondary students in Los Angeles. The study focused on the continuation and graduation rates of ethnic minority students who received special funding from the Catholic Education Foundation (CEF). Using qualitative and quantitative measures, the study revealed that students from ethnic minority and low-income communities enrolled in Catholic schools are graduating from secondary schools at a higher rate than their peers who are enrolled in public schools. Furthermore, survey data was collected from principals and parents of these students enrolled in Catholic schools. The study shows that a Catholic education has a major impact on the lives of these students, their parents, and their communities.